2015
DOI: 10.1017/ice.2015.127
|View full text |Cite
|
Sign up to set email alerts
|

Building and Validating a Computerized Algorithm for Surveillance of Ventilator-Associated Events

Abstract: The automated VAC algorithm is efficient and accurate and is ready to be used routinely for VAC surveillance. Furthermore, its implementation can optimize the sensitivity and specificity of VAC identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Although there was variability in VAC detection by these staff members, interobserver agreement as measured by the κ statistic still exceeded 0.6. Unlike the variability in VAP detection using traditional surveillance definitions, which typically arose from differences in the assessments of subjective definition criteria and was difficult to resolve, the variability in VAE detection in the Mann et al (23) study was due to readily correctable errors in applying VAC criteria. McMullen et al (24) also reported good agreement when comparing a strategy of automated VAC and IVAC detection plus manual chart review by infection preventionists for PVAPs to an approach using prospective, manual VAE surveillance by pulmonary physicians and critical care unit staff ( κ , 0.81).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although there was variability in VAC detection by these staff members, interobserver agreement as measured by the κ statistic still exceeded 0.6. Unlike the variability in VAP detection using traditional surveillance definitions, which typically arose from differences in the assessments of subjective definition criteria and was difficult to resolve, the variability in VAE detection in the Mann et al (23) study was due to readily correctable errors in applying VAC criteria. McMullen et al (24) also reported good agreement when comparing a strategy of automated VAC and IVAC detection plus manual chart review by infection preventionists for PVAPs to an approach using prospective, manual VAE surveillance by pulmonary physicians and critical care unit staff ( κ , 0.81).…”
Section: Discussionmentioning
confidence: 90%
“…The investigators also found that over a 6-month period, use of the automated method saved 94 hours of staff time when compared with the time required for manual surveillance. Similarly, Mann et al (23) found that when compared with intensivist medical record review, an automated method to identify VACs had 100% sensitivity, specificity, and positive and negative predictive values and was time efficient. However, manual VAE surveillance performed by other hospital staff (infection preventionists and an infection control fellow) in this same study was time-consuming and missed a substantial number of VACs (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manual surveillance has been shown to be less sensitive than automated surveillance for detection of VAE. 10 …”
Section: Discussionmentioning
confidence: 99%
“…studies corresponding to years previous to the 2015 update refer to possible pneumonia as a different concept as subsequent studies following the new update. Automated surveillance for ventilator-associated events through an updated electronic algorithm can help to solve some of these misunderstanding problems in addition to save hours of staff time spent in chart review (Hebert et al, 2018;Shenoy et al, 2018) but again, the terms could not to be properly used (Mann et al, 2015).…”
Section: Considerations When Reviewing Vae Research In the Literaturementioning
confidence: 99%